Improving the teenager creativity to become podcasters at the Media Kasih Islamic Orphanage, Tangerang - Munadhil Abdul Muqsith; Radita Gora Tayibnapis; Oni Tarsani (Universitas Muhammadiyah Magelang, 2023)
Recent decade, the podcast has become one of the new media platforms that have become a trend in society. Podcasts are becoming increasingly popular, especially during the Covid-19 pandemic. At a time when people are forced to social distancing, some people want to build their creativity easily and cheaply, and efficiently on various podcast platforms. Podcasts are mostly only known among urban communities, while among fostered children such as those in orphanages, they are so common and unknown. This community service aims to introduce podcasts through training for orphanage. The results obtained by fostered students at the Media Kasih Islamic Foundation Orphanage are so enthusiastic in learning about podcasts and making podcasts for their respective activities that they build their creativity.